IDENTIFICATION OF THE PROBLEMS OF PROMOTING ENVIRONMENTAL ACTIVITIES OF ENTERPRISES IN CONDITIONS OF INNOVATIVE DEVELOPMENT IN RUSSIA - G. Arakelova; A. Agafonov (Вестник университета)
In the article is revealed the most important problem of necessity for development of ecologically oriented activities of the Russian enterprises when Russia’s passing to innovative way of development. There are considered the changes of the legal framework of the Russian Federation on environmental protection in recent years. There are analyzed the problems occurred in enterprises in the process of implementation of new laws in the field of environmental protection in Russia. It is studied deficiency in legal framework in the field of environmental protection in Russia.